Carbon Dioxide and Methane Flux Response and Recovery From Drought in a Hemiboreal Ombrotrophic Fen - Keane, J. B; Toet, S.; Ineson, P.; Weslien, P.; Stockdale, J. E.; Klemedtsson, L. (Frontiers in Earth Science, 2021)
Globally peatlands store 500 Gt carbon (C), with northern blanket bogs accumulating 23 g C m-2 y-1 due to cool wet conditions. As a sink of carbon dioxide (CO2) peat bogs slow anthropogenic climate change, but warming climate increases the likelihood of drought which may reduce net ecosystem exchange (NEE) and increase soil respiration, tipping C sinks to sources. High water tables make bogs a globally important source of methane (CH4), another greenhouse gas (GHG) with a global warming potential (GWP) 34 times that of CO2. Warming may increase CH4 emissions, but drying may cause a reduction. Predicted species composition changes may also influence GHG balance, due to different traits such as aerenchyma, e.g. Eriophorum vaginatum (eriophorum) and non-aerenchymatous species, e.g. Calluna vulgaris (heather). To understand how these ecosystems will respond to climate change, it is vital to measure GHG responses to drought at the species level. An automated chamber system, SkyLine2D, measured NEE and CH4 fluxes near-continuously from an ombrotrophic fen from August 2017 to September 2019. Four ecotypes were identified: sphagnum (Sphagnum spp), eriophorum, heather and water, hypothesising that fluxes would significantly differ between ecotypes. The 2018 drought allowed comparison of fluxes between drought and non-drought years (May to September), and their recovery the following year. Methane emissions differed between ecotypes (p< 0.02), ordered high to low: eriophorum > sphagnum > water > heather, ranging from 23 to 8 mg CH4-C m-2 d-1. Daily NEE was similar between ecotypes (p> 0.7), but under 2018 drought conditions all ecotypes were greater sources of CO2 compared to 2019, losing 1.14 g and 0.24 g CO2-C m-2 d-1 respectively (p< 0.001). CH4 emissions were ca. 40% higher during 2018 than 2019, 17 mg compared to 12 mg CH4-C m-2 d-1 (p< 0.0001), and fluxes exhibited hysteresis with water table depth. A lag of 84-88 days was observed between rising water table and increased CH4 emissions. A significant interaction between ecotype and year showed fluxes from open water did not return to pre-drought levels. Our findings suggest that short-term drought may lead to a net increase in C emissions from northern wetlands.